Discrimination in the Paradigm of Crime: A Sociolegal Approach - LOZA, Yasmine (Revista Jurídica Portucalense, 2024)
Critical race theory is used to investigate the literature on victimhood and subtle and blatant prejudice in law enforcement. In the current contextual climate, the phenomenon of discrimination is explored through a sociology of law to discuss the theoretical and practical implications of justice practitioners on society. Discrimination based on gender, racial bias, ethnicity/religion, and other sociocultural markers of difference is an ongoing process which must urgently be considered and treated as a structural concern in society and distinctly, in legal frameworks embedded as police and victim paradigms. The diffusion of fear and stereotypes of a constructed ‘other’ has been pronounced since historical narratives until the contemporary moment to portray power imbalances and victim-blaming attitudes which reinforce favouritism of certain identities and silence others. Discourses of (dis)empowerment are perpetuated in knowledge apparatus which produce and subject the ‘other’ into a category of inferiority evident in judgments of crime. Racism and the perpetuity of racist discourses are in this way critically redressed to reveal the significance of multidisciplinary approaches in socio-legal frameworks and the interwoven potentials of justice to protect all identities as human beings.